Decoding the results of the Ridge Trace method for nonorthogonal linear models into practical predicting coefficients - Sampaio, Ivan Barbosa Machado (Pesquisa Agropecuaria Brasileira, 2014)
The troublesome task of decoding the coefficients obtained from the Ridge Trace method for nonorthogonal models when k > 0 can be easily resolved by using the decoding factor Cβ1 = normal coefficient/standardized coefficient, both terms calculated by the least square procedure. A non-significant amount of error is then introduced but recovering the coefficients in their original unities for a practical predicting equations surmounts this objection. The intercept of the final equation is obtained in the usual way. A FORTRAN program on the method is added allowing quick data computation and further basis for decoding coeficients.
Keywords: Nonorthogonal linear models; Ridge Trace method; predictivy coefficients; standardized variable; decoding factor